2016
DOI: 10.1016/j.indcrop.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents of leaf extracts of Ziziphus jujuba Mill. plants harvested in Tunisia

Abstract: The present study aimed to determine the phytoconstituent compositions of the leaves of four Ziziphus jujuba ecotypes (Choutrana, Mahdia, Mahres and Sfax). The chromatographie peaks of 18 compounds, including nine major fatty acids, live sterols, two triterpene alcohols and two methysterols, were quan tified by the capillary gaseous chromatography method. The major fatty acids identified were linolenic (42.04%) and palmitic (23.04%). Unsaturated fatty acids ranged between 53% and 60%. The predominant sterols (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…The extraction method described previously [23, 24] has been used with a slight modification. Briefly, 25 g of the powder of each plant was macerated in 250 ml of methanol under agitation of 500 rpm at room temperature for 6 h. The resulting mixture was filtered using Whatman filter paper n°1 and then evaporated under vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction method described previously [23, 24] has been used with a slight modification. Briefly, 25 g of the powder of each plant was macerated in 250 ml of methanol under agitation of 500 rpm at room temperature for 6 h. The resulting mixture was filtered using Whatman filter paper n°1 and then evaporated under vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…However, our findings in a previous study show that aqueous extracts have not shown any antibacterial activity due to the influence of solvents nature and polarity. For this reason, ethanol extracts of the seventeen most common plants cited by the healers (FI≥8.88%) have been prepared in accordance to the methods described by Elaloui et al and Yeo et al with slight modifications [17,18]. The used part of each plant as mentioned by herbalists was grounded to powder, and then 10 g of the powder of each plant was macerated in 100 ml of ethanol under agitation (500 rpm), at room temperature for 6 h. The resulting mixture was filtered through Whatman filter n°1 then evaporated under vacuum.…”
Section: Plants Selection and Preparationmentioning
confidence: 99%
“…Ziziphus jujuba Mill. (Rhamnaceae) is one such plant used by traditional healers for the treatment of liver ailments, cancer, diabetic complications, insomnia, anemia, diarrhea, and loss of appetite ( Elaloui et al, 2016 ). This plant possesses different chemical components like alkaloids, flavonoids, glycosides, and phenolic group of compounds ( Yoshikawa et al, 1997 ; Pawlowska et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%